Синтез ряду іліденпохідних 4-аміно-3-(морфолінометилен)-4Н-1,2,4-триазол-5-тіолу - Щербина, Роман Олександрович; Панасенко, Олександр Іванович; Книш, Євгеній Григорович; Shcherbyna, R. О.; Panasenko, O. I.; Knysh, Ye. H. (My University, 2014)
Синтетичні трансформації гетероциклічних систем з метою розроблення біологічно активних агентів стали фундаментальною основою активно прогресуючого наукового напряму тонкого органічного синтезу та медичної хімії. У цьому контексті високий теоретичний і практичний інтерес представляють похідні 4-аміно-1,2,4- триазол-5-тіолу, оскільки вони виявляють протизапальну, жарознижувальну, аналгезуючу, протимікробну та протитуберкульозну дію [1, 2, 3]. До теперішнього часу накопичено досить великий масив даних із синтезу, будови та біологічних властивостей різних похідних 4-аміно-1,2,4-триазол-5-тіолу [2, 4, 5], проте слід зазначити, що маловивченими залишаються похідні 4-аміно-3-(морфолінометилен)- 4H-1,2,4-триазол-5-тіолу. З джерел літератури відомо [1, 2, 4, 5], що наявність в молекулі азометинового фрагмента підвищує протимікробні властивості сполук. А тому ми вважали за доцільне синтезувати новий ряд іліденпохідних 4-аміно-3-(морфолінометилен)-4H-1,2,4-триазол-5-тіолу, для яких планується зробити дослідження протимікробних та протигрибкових властивостей. Synthetic transformations of heterocyclic systems in order to develop biologically active agents have become the fundamental basis of actively progressing scientific direction of thin organic synthesis and medicinal chemistry. In this context, a highly practical and theoretical interest are represents the derivatives of 4-amino- 1,2,4-triazole-5-thiol since they shows anti-inflammatory, antipyretic, analgesic, antimicrobial and anti-T B activities. Therefore, the synthesis new row of ylidenederivatives of 4-amino-3-(morpholinomethylene)-4H- 1,2,4-triazole-5-thiol is very important. The purpose of this research is synthesis of new row ylidenederivatives 4-amino-3-(morpholinomethylene)- 4H-1,2,4-triazole-5-thiol, and confirmation of their structure. Study of the physicochemical properties of the synthesized compounds carried out according to the State Pharmacopoeia of Ukraine. Melting points were determined by open capillary method on instrument OptiMelt MPA 100. The elemental composition of the synthesized compounds were established on the analyzer Elementar Vario L cube (CHN S) . 1H NM R spectra of the compounds were filmed by using a spectrometer Varian Mercury VX-200. Chromatography-mass spectral studies were carried out on gas-liquid chromatography Agilent 1260 Infinity HP LC with mass spectrometer Agilent 6120. As the result of research new 23 compounds are synthesized namely potassium 2-(2-morpholinoacetyl) hydrazinecarbodithioate, 4-amino-3-(morpholinomethylene)-4H-1,2,4-triazole-5-thiol and 4-(R-ylidenamino)- 3-(morpholinomethylene)-4H-1,2,4-triazole-5-thiols. The structure of the synthesized compounds were confirmed in all cases by modern instrumental analysis methods (1H NM R-spectroscopy, chromatography-mass spectrometry and element analysis), and the obtained compounds may further be used in biological research.
Synthesis of row ylidenederivatives 4-amіno-3-(morfolіno-methylen )-4h-1,2,4-trіazol-5-thіol
Keywords: органічний синтез; іліденпохідні; 1,2,4-триазоли; organic synthesis ylidenederivatives; 1,2,4-triazole